2001
DOI: 10.3348/kjr.2001.2.3.151
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging-Histopathologic Correlation of Radiofrequency Thermal Ablation Lesion in a Rabbit Liver Model: Observation during Acute and Chronic Stages

Abstract: Objective: To determine the ability of MR imaging to detect the pathological changes occurring in radiofrequency (RF) thermal lesions and to assess its accuracy in revealing the extent of tissue necrosis. Materials and Methods:Using an RF electrode, thermal lesions were created in the livers of 18 rabbits. The procedure involved three phases. In the acute phase, six animals were killed the day after performing thermal ablation with RF energy, and two on day 3. In the subacute and chronic phases, eight rabbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 24 publications
4
90
0
1
Order By: Relevance
“…The increase in false positive findings originated from perilesional parenchymal insults that showed sustaining hyperintensity on DWI with increasing b factors. Because a lesion-to-lesion correlation between DWI and histological features was not possible in this study, the mechanism for the high false positive rate with DWI could be just speculated as perilesional inflammation, which is more frequently noted after radiofrequency ablation (25) and may result from TACE (19,26). Hypercellularity intermingled with a fibrotic component in the inflammatory granulation tissues could restrict water diffusion, resulting in sustaining hyperintensity on DWI (27).…”
Section: Discussionmentioning
confidence: 90%
“…The increase in false positive findings originated from perilesional parenchymal insults that showed sustaining hyperintensity on DWI with increasing b factors. Because a lesion-to-lesion correlation between DWI and histological features was not possible in this study, the mechanism for the high false positive rate with DWI could be just speculated as perilesional inflammation, which is more frequently noted after radiofrequency ablation (25) and may result from TACE (19,26). Hypercellularity intermingled with a fibrotic component in the inflammatory granulation tissues could restrict water diffusion, resulting in sustaining hyperintensity on DWI (27).…”
Section: Discussionmentioning
confidence: 90%
“…Because of the impracticality of repeated injections, the extent of the ablative zone can only be assessed at the end of the procedure. It has also been suggested that magnetic resonance imaging (MRI) can be used to guide RF ablation by acquiring unenhanced images, especially T2-weighted (T2w) images during the procedure (5,6). However, the limited precision of such images necessitates the acquisition of dynamic gadolinium (Gd)-enhanced T1-weighted (T1w) images at the end of the procedure (6).…”
mentioning
confidence: 99%
“…Lee et al (33) showed that the size of coagulative necrosis increases during the first week after the intervention and then begins to gradually decrease. An involution of the coagulation zone could have taken place before the follow-up examination.…”
Section: Discussionmentioning
confidence: 99%
“…Nonenhanced areas in these images were regarded as necrotic tissue (22,23). Concerning the temperature maps, we considered that tissue that reached at least 60°C could be regarded as necrotic.…”
Section: Segmentation Of the Coagulation Zonementioning
confidence: 99%